A History of Lutheranism - Gritsch, Eric W. (Minneapolis Fortress Press, 2002)
In a nontechnical way, noted Reformation historian Gritsch tells the story of how the Christian reforming and confessional movement survived its first battles with religious and political authorities to become institutionalized in its religious practices and teachings.
Keywords: Lutheran Church -- Doctrines -- History. Lutheran Church -- Doctrines. Lutheranisme